Tāʾiyya-yi ʿAbd al-Raḥmān-i Jāmī : Tarjuma-yi Tāʾiyya-yi Ibn-i Fāriḍ bih inḍimām-i sharḥ-i Maḥmūd-i Qayṣarī bar Tāʾiyya-yi Ibn-i Fāriḍ - al-Fāriḍ, Ibn (Miras Maktoob, ISBN: 9789004365452., 2019)
Ibn al-Fāriḍ (d. 632/1235) is arguably the greatest mystical poet in the history of Arabic literature. Born in Cairo and a student of Shāfiʿī law and ḥadīth in his younger years, he turned to mysticism, living a solitary existence on Cairo's Muqaṭṭam hills, in the desert, and in the Hijaz. After his return to Cairo, people worshipped him as a saint and even today, admirers still visit his tomb in that city. ʿAbd al-Raḥmān Jāmī (d. 898/1492) is one of Persia's great medieval poets. As a young man, he joined the followers of Saʿd al-Dīn Kāshgharī (d. 860/1456), leader of the mystical Naqshbandiyya order in Herat. His combined output in poetry (39.000 lines of verse) and prose (over 30 works) is quite overwhelming. Besides a commentary on Ibn al-Fāriḍ's Khamriyya mīmiyya , he also made the first and only Persian translation of his seminal al-Tāʾiyya al-kubrā , published here for the very first time.